Penerapan Grup "TERASU" (Terapi Suportif) pada Lansia Hipertensi dengan Depresi - Pastari, Marta; Endriyani, Sri; Martini, Sri; Somad, Abdul; Aflika, Dodi; Meilina, Meilina; Ningsih, Ratna (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
Depression usually occurs in the elderly with primary hypertension. In people with hypertension, depression causes a decrease in health status, quality of life and social role function. Hypertension has become a public health problem that has continued to increase in the last 20 years. Data from the World Health Organization (WHO) in 2015, around 1.13 billion people worldwide have hypertension (Pradono, 2020). In Indonesia, there were 63,309,620 cases of hypertension and 427,218 deaths due to hypertension. The prevalence of hypertension in South Sumatra Province is 35.8%, with 1432 cases in 2019 to 3981 cases and 4631 cases in 2020. Data on elderly people with hypertension and depression in 2024 in the Ariodillah Health Center work area is still high, which is around 70% of the total elderly (Puskesmas Ariodillah, 2024). Combination interventions of psychotherapy and pharmacotherapy in individuals, families and groups can help reduce symptoms of depression, especially in the elderly. This is reinforced by research (Tobing & Novianti, 2019) that the intervention group with supportive group therapy experienced a significant decrease in hypertensive stress levels. The solutions to the problems offered in this community service activity are in the form of; Coordination of the implementation of activities including preparation of the place of implementation, time and number of participants who can attend the activity. Preparation of supportive therapy modules, leaflets and blood pressure measuring devices; Implementation; Activities in the form of supportive therapy training are carried out in 4 sessions, namely; The first session, carried out with the aim of exploring the problems of the elderly and identifying the support systems that the elderly have. The second session, the use of the support system identified in session 1 owned by the elderly, monitoring its use and obstacles. In the second session of this supportive therapy, the servant and the elderly discuss the support system that exists within the elderly to solve problems and how to use it. The third session, using the support system that exists outside the elderly. This session identifies the support system that exists outside the elderly and teaches how to use it. The fourth session, evaluates how the elderly use the support system and the obstacles in using the support system. In this session, the elderly are asked to convey all the sources of support they have and convey the obstacles or barriers they face. At the end of the session, the servant evaluates and follows up with the elderly on the internal and external sources of support that they have and have practiced. Termination is the final stage of each session of this activity. The activities carried out are to evaluate by asking the elderly how they feel after gaining knowledge and skills to overcome emotional mental disorders. Based on the target achievements and results of the activities, it can be concluded that after the intervention was given, the results of the activities showed that; a) 39% of the elderly still experienced hypertension with moderate depression and 61% of the elderly were in a normal state (no longer depressed); b) Non-pharmacological therapy (Group Supportive Therapy) is used as routine therapy for the elderly at the Elderly Posyandu in the Ariodillah Health Center working area; c) 100% of the elderly have been educated and accompanied regarding the use of supportive group therapy and are required to apply it as daily therapy at home. The follow-up to this activity is that health cadres will accompany all heads of families in stages to apply supportive group therapy in their respective homes and motivate the elderly to routinely participate in activities at the Elderly Posyandu.